LIFESTYLE BUSINESSES IN REZEKNE MUNICIPALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In regional economy, creation of a system for development of small enterprises and lifestyle businesses is one of the strategies to promote entrepreneurship and targeted use of the local economic resources thus reducing the burden on public and local budgets. Lifestyle businesses are mainly established and maintained with the aim of providing a certain level of income, performing additional activities or developing the owner's hobby, and effectively using the local resources. The aim of the research is to explore the theoretical foundations of lifestyle businesses and potential for their creation and development, using lifestyle businesses of Rezekne municipality as a case. The following tasks were set for achieving the aim: to provide theoretical rationale for lifestyle businesses; to identify lifestyle businesses in Rezekne municipality; to study and analyse the motivation of lifestyle business owners to establish and develop business in Rezekne municipality.